Preserving a Healthy Ecohydrology: a Legal Perspective - Md Khalid, Rasyikah; Jaria Maidin, Ainul; Sarah Sulaiman, Siti (International Journal of Engineering and Technology, 2018)
Ecohydrology focuses on ecological processes within the hydrological cycle. It works under the assumption that an anthropogenically modified catchment or river basin can reverse environmental degradation and enhance the ecosystem service through improved climate cycle, controls erosion, soil formation, water purification, waste treatment and food production. Improved ecosystem services within the hydrological cycle can also serves humanâ€™s cultural and spiritual aspect as well as in the production of scientific knowledge. There has been call for countries to regulate the use of ecosystem as they are being degraded faster than they can recover. In 2001, the United Nations Environmental Program (UNEP) initiated the Millennium Ecosystem Assessment (MEA) to assess the consequences of ecosystem change for human well-being. It finds that 60% of 24 ecosystem services examined such as clean water, food, forest products, flood control and provision of natural resources has been badly degraded due to unsustainable development. It is submitted that law can play a role in ensuring preservation of a healthy ecohydrology as a tool used by respective authorities to achieve sustainable development and prevent excessive use of natural resources. This requires a new philosophy on the role of law in ecohydrological protection since environmental legislations fail to punish human activities that had either directly or indirectly disrupt the normal hydrological cycle. An analysis on earth jurisprudence, environmental ethics, equity and justice may elucidate the need to preserve a heathy ecohydrology as its own and other humanâ€™s right.Â Â